Relationship between Collage Activities and Early Children’s Creativity - Sapaat, Siti (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
This study aims to determine the relationship between college activities and early childhood creativity in the Islamic Kindergarten of Asy Syifa, Cikancung District, Bandung Regency. The method used in this study is the correlation method with a quantitative approach, sampling techniques using saturated sampling techniques, data collection techniques using observation, and data analysis using statistical formulas. This research is motivated by preliminary studies conducted in the Islamic Kindergarten of Asy Syifa that children's creativity is still low, evidenced by the average value obtained is 2.3, which is in the range of 1.75-2.49, which is interpreted to begin to develop. The activity that has been running in the learning process in the Islamic Kindergarten of Asy Syifa to train children's creativity is collage. Based on the analysis of college activity data obtained, an average value of 74.15 is categorized as good. Early childhood creativity obtained an average value of 2.78, categorized as developing according to expectations. Then the value of thing = 25.52 > table = 2.160 at a significant level of 5% interpreted Ho rejected, and Ha accepted means there is a significant relationship between college activities and early childhood creativity in the Islamic Kindergarten of Asy Syifa. It obtained a correlation coefficient of 0.99, which is interpreted as very strong. The contribution of collage activities to early childhood creativity was 98%, and other factors influenced 2%. Abstrak Penelitian ini bertujuan untuk mengetahui hubungan antara kegiatan membuat kolase dengan kreativitas anak usia dini di Raudhatul Athfal Asy Syifa yang berlokasi di Kabupaten Bandung, Indonesia. Metode yang digunakan dalam penelitian ini adalah metode korelasi dengan pendekatan kuantitatif, teknik pengambilan sampel menggunakan teknik sampling jenuh, teknik pengumpulan data menggunakan observasi, dan analisis data menggunakan rumus statistik. Penelitian ini dilatarbelakangi oleh hasil studi pendahuluan yang dilakukan di Raudhatul Athfal Asy Syifa bahwa kreativitas anak masih rendah, hal ini dibuktikan dengan nilai rata-rata yang diperoleh adalah 2,3 yang berada pada rentang 1,75 - 2,49 yang ditafsirkan Mulai Berkembang. Kegiatan yang berjalan dalam proses pembelajaran di Raudhatul Athfal Asy Syifa untuk melatih kreativitas anak adalah kolase. Berdasarkan hasil analisis data, kegiatan kolase memperoleh nilai rata-rata 74,15, dikategorikan Baik. Kreativitas anak usia dini memperoleh nilai rata-rata 2,78, dikategorikan Berkembang Sesuai Harapan. Kemudian nilai thitung = 25,52 > ttabel = 2,160 pada taraf signifikan 5% yang diinterpretasikan Ho ditolak dan Ha diterima, artinya terdapat hubungan yang signifikan antara kegiatan kolase dengan kreativitas anak usia dini di Raudhatul Athfal Asy Syifa. Diperoleh nilai koefisien korelasi sebesar 0,99 yang diinterpretasikan sangat kuat. Kontribusi kegiatan kolase terhadap kreativitas anak usia dini di Raudhatul Athfal Asy Syifa sebesar 98%, dan faktor lain mempengaruhi sebesar 2%.